2020
DOI: 10.14499/indonesianjcanchemoprev11iss2pp97-10
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Potential of Flavonoid from Nicotiana tabacum Leaves on MCF-7 Human Breast Cancer Cells

Abstract: Flavonoid has potential bioactivity as anticancer agents. The flavonoid of cultivated tobacco (Nicotiana tabacum), locally known as “Kasturi”, leaves was screened for its cytotoxicity against MCF-7 human breast cancer cells and non-transformed Vero cells (African normal cell kidney line) in different concentrations. This study aimed to examine the cytotoxic potential of the flavonoid of Kasturi tobacco leaves against MCF-7 human breast cancer cells. Flavonoid obtained from methanolic extracts of Kasturi tobacc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The study of Al-Lahham [12] showed that the aqueous and methanol extracts of N. tabacum L. roots have an anti-proliferative effect on HeLa cervical adenocarcinoma. Also, the flavonoid extract of N. tabacum L. leaves has a potent cytotoxic effect on MCF7 human breast cancer cells [17]. The study conducted by Obare [28] showed that the aqueous acetone extract of N. tabacum L. stems has a toxic effect on some human cancer cell lines such as human alveolar basal epithelial cells adenocarcinoma (A549), prostate cancer cell line (PC3), and MCF7.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study of Al-Lahham [12] showed that the aqueous and methanol extracts of N. tabacum L. roots have an anti-proliferative effect on HeLa cervical adenocarcinoma. Also, the flavonoid extract of N. tabacum L. leaves has a potent cytotoxic effect on MCF7 human breast cancer cells [17]. The study conducted by Obare [28] showed that the aqueous acetone extract of N. tabacum L. stems has a toxic effect on some human cancer cell lines such as human alveolar basal epithelial cells adenocarcinoma (A549), prostate cancer cell line (PC3), and MCF7.…”
Section: Discussionmentioning
confidence: 99%
“…The α-CBD isolated from tobacco can reduce the formation of cell clones and inhibits the proliferation of hepatocellular carcinoma cells in the S phase of mitotic division, change cell shape, and change the permeability of membranes [16]. The flavonoid isolated from tobacco leaves has cytotoxic activity on (MCF-7)cells and can be a potential agent for human breast cancer therapy [17].…”
Section: Introductionmentioning
confidence: 99%
“…(1-4) Ethnopharmacological reports indicate that tobacco leaves have been used as traditional medicine, and recent studies have found that tobacco leaves have anti-cancer properties. (5)(6)(7)(8) The contribution of the bioactive components in tobacco as anti-tumor in modern medicine can not be ignored. Recently, the use of α-2,7,11-cyprotermine-4,6-diol (α-CBD) from tobacco has been evaluated in hepatocellular carcinoma cells in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…These results indicate that flavonoids are more selective against breast cancer cells than normal cells, so that flavonoids in tobacco leaves can be considered as potential chemotherapeutic or chemopreventive agents based on their ability to induce apoptosis in breast cancer cells with relatively low toxicity to normal cells. (7) Cervical cancer is the fourth most common cancer in women caused by Human Papilloma Virus (HPV), which can affect cell proliferation and apoptosis. (9) Molecular studies revealed viral oncoproteins, E6 and E7, interfere with the tumor suppressor genes p53 and pRb.…”
Section: Introductionmentioning
confidence: 99%